2022
DOI: 10.3354/cr01656
|View full text |Cite
|
Sign up to set email alerts
|

Population responses to harvesting in fluctuating environments

Abstract: Achieving sustainable harvesting of natural populations depends on our ability to predict population responses to the combined effects of harvesting and environmental fluctuations while accounting for other internal and external factors that influence population dynamics in time and space. Here, we review recent research showing how spatial patterns and interspecific interactions can influence population responses to harvesting in fluctuating environments. We highlight several pathways through which harvesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 156 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…This study was inspired by our previous results on spatial population synchrony [31][32][33][34] and motivated by the findings that population fluctuations showed larger predictability than the underlying environmental variables. This was shown to happen for a wide range of systems: primary production in oceans [25], crop yield [26], malaria [27] and fisheries [28].…”
Section: Discussionmentioning
confidence: 99%
“…This study was inspired by our previous results on spatial population synchrony [31][32][33][34] and motivated by the findings that population fluctuations showed larger predictability than the underlying environmental variables. This was shown to happen for a wide range of systems: primary production in oceans [25], crop yield [26], malaria [27] and fisheries [28].…”
Section: Discussionmentioning
confidence: 99%
“…An important question is how the effects of harvesting interact with ongoing climate change (Gamelon et al 2019), for instance through age-or sexspecific sensitivities to climate variation (Herfindal et al 2015, Lee et al 2021 in this Special). However, because range shifts or changes in large-scale movement patterns such as seasonal migrations are central mechanisms in animals' responses to climate change (Morrison et al 2021), the study at Vega may be less ideal for generating general results about harvesting under climate change.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, age structure and the form of density-dependent mortality among life history stages can also substantially change the stability properties of non-linear models (Liz & Pilarczyk, 2012). In contrast, models and a reindeer case study have also shown that harvesting can dampen population fluctuations due to the specifics of life history and density dependence (Lee et al, 2022;Peeters et al, 2022). Alternatively, fluctuations can be elevated by a shift in demographic parameters that alter how to process noise interacts with non-linear deterministic processes.…”
Section: Introductionmentioning
confidence: 99%